Controlling Friction With External Electric or Magnetic Fields: 25 Examples - Krim, Jacqueline (Frontiers in Mechanical Engineering, 2019)
Studies of the fundamental origins of friction have progressed rapidly in recent years, yielding valuable information on the relative contributions of electronic, magnetic, electrostatic, and phononic dissipative mechanisms. The field is now moving toward design of active control method for nano and/or meso scale friction, including the use of magnetic and electric fields external to the contact. These methods constitute an area of rapidly growing interest, as they address one of tribology's present day grand challenges: achieving in situ control of friction levels without removing and replacing lubricant materials situated within inaccessible confines of a contact. In this review, 25 examples of electromagnetic tuning of friction are overviewed, with examples spanning atomic to macro scale systems to demonstrate the variety and versatility of approaches that have been reported in the literature. Applications include, but are not limited to triboelectric generators, geological drilling, automotive braking and efficiency, spacecraft systems, biological systems, and magnetic spintronics. Experimental methods for measuring the impact of electric or magnetic fields on friction include AFM, SFA, QCM, pin-on-disk, hard disk head-on-substrate, MEMS and NEMS based tribometers, and optical spectroscopies. Computational and theoretical approaches include analytic, equilibrium and non-equilbrium Monte Carlo simulations.